Risk Factors for Tube Shunt Exposure: A Matched Case-Control Study - Michael S. Koval; Fouad F. El Sayyad; Nicholas P. Bell; Alice Z. Chuang; David A. Lee; Stephen M. Hypes; Davinder S. Grover; Laura A. Baker; Stephen M. Huddleston; Donald L. Budenz; Robert M. Feldman (Journal of Ophthalmology)
Purpose. To evaluate potential risk factors for developing tube shunt exposure in glaucoma patients. Patients and Methods. Forty-one cases from 41 patients that had tube shunt exposure from 1996 to 2005 were identified from the Robert Cizik Eye Clinic and Bascom Palmer Eye Institute. Each case was matched with 2 controls of the same gender and with tube shunts implanted within 6 months of the index case. Conditional logistic regression was used to determine risk factors. Results. The study cohort includes a total of 121 eyes from 121 patients. The mean age was 63.6 ± 19.7 years, ranging from 1 to 96 years. The average time to exposure was 19.29 ± 23.75 months (range 0.36–85.74 months). Risk factors associated with tube exposure were Hispanic ethnicity (P=0.0115; OR = 3.6; 95% CI, 1.3–9.7), neovascular glaucoma (P=0.0064; OR = 28.5; 95% CI, 2.6–316.9), previous trabeculectomy (P=0.0070; OR = 5.3; 95% CI, 1.6–17.7), and combined surgery (P=0.0381; OR = 3.7; 95% CI, 1.1–12.7). Conclusions. Hispanic ethnicity, neovascular glaucoma, previous trabeculectomy, and combined surgery were identified as potential risk factors for tube shunt exposure. These potential risk factors should be considered when determining the indication for performing tube shunt implantation and the frequency of long-term followup.